The affects of forgiveness on the symptoms of posttraumatic stress disorder as a result of sexual trauma - Johnston, Sandra K. (My University, 2007)
This study continues research pertaining to the affects of forgiveness on Posttraumatic Stress Disorder (PTSD) symptoms resulting from sexual trauma. The research question asked whether or not the ability to forgive would reduce, increase, or have no affect upon PTSD symptoms. The hypotheses stated that the ability to forgive a specific traumatic sexual offense would correlate with fewer symptoms of PTSD, while the inability to forgive a specific traumatic sexual offense would correlate with a greater number of PTSD symptoms. Participants consisted of females eighteen and older, who had experienced sexual trauma, and stated that they had either forgiven or not forgiven their perpetrator/s. The first group was named “forgive”, and the second “unforgive”. Instruments included, a Demographic Survey, Offense Specific Forgiveness Measure, and Posttraumatic Stress Disorder Symptoms Self Inventory. Within group data analysis was performed using the Pearson’s Product-Moment Correlation; between group data was analyzed using the t-test for r. Within group correlations for both group “forgive” and “unforgive” yielded strong but insignificant results. When raw from both groups were combined, the resulting analysis showed no significant results. Between group data analysis, indicated a significant difference in forgiveness. There was no significant difference between groups for the dependent variable – PTSD. Results were carefully interpreted and were not used to predict or establish causation as they were not large enough to imply any relationship between the variables. The small number of participants as well as the predominantly white sample limited generalizations. Demographic data indicated that individuals with stated religious affiliation were less forgiving than those with no stated religious affiliation. Those same individuals were also traumatized as adults rather than as children/adolescents. The sample was predominantly white individuals with post-high school level education. The majority of perpetrators were outside of the biological family. Group “forgiveness” scores indicated an inverse relationship between variables, supporting the hypothesis, while group “unforgive” scores did not. Between group scores indicated support for the correlation between stated forgiveness and actual forgiveness, while analysis of PTSD raw scores between groups was not significant. Mental health implications begin with the importance of age at occurrence of trauma, impacting the ability to forgive. It may be beneficial for researchers to study forgiveness across the lifespan, how forgiveness and unforgiveness are learned, cultural influence on learning, and the impact of education level upon forgiveness ability indicating how practitioners can utilize the most effective forgiveness interventions. Second, the spiritual belief of the client influences expressed and actual forgiveness. Forgiveness is a choice which empowers survivors of trauma. Although not every intervention is appropriate for every client, research supports the use of forgiveness intervention as an adjunct to mental health practice. Finally, further research into the impact of forgiveness interventions, their reliability and validity, and the long-term effects will aid clinicians in determining the part forgiveness will play in practice.
Keywords: Sexual abuse victims -- Psychology; Post-traumatic stress disorder -- Patients -- Rehabilitation; Forgiveness